Cleaner production technologies for the amelioration of soil health, biomass and secondary metabolites in Ocimum basilicum L. under Indian Western Himalaya - Raj, Yog; Ali, Nilofer; Pati, Aparna Maitra; Kumar, Rakesh (Frontiers in Plant Science, 2022)
Ocimum basilicum L. and its derived products are primarily consumed by humans; hence agrochemical use seems inappropriate for its cultivation. However, farmers are accustomed to using rampant inorganic fertilizers to augment crop productivity which unintendedly engendered severe environmental perturbations. Concomitantly, farmers will soon have to confront the challenges of growing crops under suboptimal conditions driven by global climate change. Consequently, to develop a clean, sustainable, and resilient production technology, field experiments spanning over two years (2020 and 2021) were conducted comprising three biostimulants, viz., vermicompost (0, 4, and 8 Mg ha–1), biofertilizer (uninoculated and inoculated), and liquid seaweed extract (without and @ 7 mL L−1) in the Indian western Himalaya, for the first time. Soil health indicators, leaf photosynthetic pigments, gaseous exchange, mineral contents, essential oil (EO) quantity, and composition were evaluated. Soil microbial respiration (SMR), microbial biomass carbon (MBC), organic carbon (OC), dehydrogenase (DHA), alkaline phosphatase (ALP), and β-glucosidase activities were increased by 36.23, 83.98, 30.61, 42.69, 34.00, and 40.57%, respectively when compared with the initial soil status. The net photosynthetic rate (Pn) was significantly increased with the highest (8 Mg ha–1) and moderate (4 Mg ha–1) vermicompost dosages by 13.96 and 4.56%, respectively, as compared with the unfertilized control (0 Mg ha–1). Likewise, the biofertilizer and seaweed extract also enhanced Pn by 15.09 and 10.09%, respectively. The crop's key EO constituents, viz., methyl chavicol and linalool, were significantly improved with the highest and moderate vermicompost rates by 2.71, 9.85%, and 1.18, 5.03%, respectively. Similarly, biofertilization and seaweed application also boosted methyl chavicol and linalool by 3.29, 8.67%, and 1.93, 3.66%, respectively. In both years, significantly higher herbage (8.86 and 11.25 Mg ha−1) and EO yield (113.78 and 154.87 kg ha−1) were recorded with a congregate treatment of the highest vermicompost dose, biofertilizer, and liquid seaweed extract. In conclusion, the integrated use of biostimulants having complementary properties can sustainably maximize the quantity and quality of O. basilicum and concomitantly ameliorate soil health. This study can impute scientific communities and industries to develop second-generation biostimulant products delivering better sustainability and resilience for a renaissance in agriculture.